2000
DOI: 10.1021/cm0003370
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-PECVD Films from Hexamethylcyclotrisiloxane for Use as Insulating Biomaterials

Abstract: Thin films produced by plasma-enhanced chemical vapor deposition (PECVD) have potential application as conformal coatings on implantable devices with complex topologies and small dimensions. Coatings on such devices need to be biocompatible, insulating, and flexible enough to minimize static forces on the surrounding tissue. In this study, we describe the use of pulsed-PECVD to deposit thin films from hexamethylcyclotrisiloxane (D3). Pulsed-PECVD is a method in which plasma excitation is modulated to favor dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…Deposition was carried out under low vacuum conditions, with low chamber pressure (0.03 Torr), low argon flow rate (99.99% purity, flow rate of 10 cm 3 /min), and low radio frequency power (30 W) . The RF power was pulsed with frequency ranging between 100 to 1000 Hz and duty cycles ranging from 25% to 100%, because previous studies have reported that using a low power pulsed plasma helps the activation as well as the retention of chemical activity of the deposited molecule . The morphology of the PECVD deposited di‐ d ‐phenylalanine nanotubes are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Deposition was carried out under low vacuum conditions, with low chamber pressure (0.03 Torr), low argon flow rate (99.99% purity, flow rate of 10 cm 3 /min), and low radio frequency power (30 W) . The RF power was pulsed with frequency ranging between 100 to 1000 Hz and duty cycles ranging from 25% to 100%, because previous studies have reported that using a low power pulsed plasma helps the activation as well as the retention of chemical activity of the deposited molecule . The morphology of the PECVD deposited di‐ d ‐phenylalanine nanotubes are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although methyl abstraction was considered to be the key step in “continuous wave” (as opposed to pulsed) ppt for monomers such as HMDSO and HMDSN, the pulsed ppt of hexamethylcyclotrisiloxane showed complete absence of methylene groups in the resultant pps . The hexamethylcyclotrisiloxane pp incorporated Si(CH 3 ) 2 elements as part of the growing pp network during pulsed polymerization . Hence, it is important to also consider the effect of the molecular structure of the monomer on the final pp.…”
Section: Siloxane Plasma Polymersmentioning
confidence: 99%
“…Pulsing a plasma discharge may induce alterations of the discharge chemistry, which depend on the time the discharge is active, t ON , the time it is unlit, t OFF , and the duty cycle DC = t ON /( t OFF + t ON ), where ( t ON + t OFF ) is the period. A film deposited by pulsed plasma can have significant different properties than one deposited by continuous plasma as largely demonstrated in the literature 16, 17. In PECVD processes with high fragmentation regimes, during the ON‐time the polymer growth is fast and the film is subject to positive ion bombardment, UV‐radiation and to the interactions with many unstable species and fragments.…”
Section: Resultsmentioning
confidence: 99%